Sistem Operasional Akad Ijarah Pada Kinerja Tukang Bangunan Menurut Ekonomi Islam di Desa Kertagena Tengah Kabupaten Pamekasan - Fakhruzy, Agung (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
The house-building business in the Central Kertagena Village is one of the businesses that are of concern to the community by using a timing system with "Ijarah" payments. The homeowner gives a verbal description to the builder then gives according to the specified promise. Parties in association do not know about contracts Many conflicts occur due to rules that must be followed by both parties not working properly. And also the compilation of goods has been completed does not match the owner and the builder did not want to admit his mistakes. Based on this, there are two that are the focus of this study, first: How is the application of the ijarah contract to the performance of builders in the village of Central Kertagena? The results showed that in the implementation of the contract at the beginning of the agreement only based on verbal and not published in accordance with the problem at the end after the completion of the contract. Then at 07:00 WIB - 04:00 WIB. However, it is satisfied to repair the building that was built over that time and stopped before the traffic jams, as well as to repair the house and cost more. In addition, the lack of clarity in the good model of the house model of the homeowner ordered the desired goods only by word alone and the builder requires no need to be correct so that more causes problems. When the goods are finished it is not suitable for the owner and the builder does not want to admit his mistakes.